Suburban Equilibrium - Dohrmann,Benjamin (2019)
Explores the origins of suburban expansion and identifies 9 key ‘symptoms’ of urban sprawl – including car dependency, social isolation and monofunctional neighbourhoods. The research is based on a site location of Deer Park in Melbourne, Australia. By making proposals at the metropolitan, district, neighbourhood and block scales the aim is to challenge these symptoms, thereby improving the function of the city generally and giving people the opportunity to raise their standard of living. This is made through four key strategies - connectivity, streetscape repair, parkland repair, housing renewal. The site proposals are made along themes such as small scale interventions, local production, small businesses, new meeting places and collective housing. This is explored with pilot developments that facilitate participation between neighbours and government agencies by lot consolidation with new housing and employment typologies.
Keywords: urban; sprawl; suburbs; neighbourhood; planning; urban design; densification; development; sustainable; design; collective housing; suburban typologies